Open Platform Concept for Blockchain-Enabled Crowdsourcing of Technology Development and Supply Chains - Ducrée, Jens; Gravitt, Max; Walshe, Ray; Bartling, Sönke; Etzrodt, Martin; Harrington, Tomás (Frontiers in Blockchain, 2020)
We outline the concept of an open technology platform that builds upon a publicly accessible library of fluidic designs, manufacturing processes, and experimental characterization, as well as virtualization by a “digital twin” based on modeling, simulation, and cloud computing. Backed by the rapidly emerging Web3 technology “Blockchain,” we significantly extend traditional approaches to effectively incentivize broader participation by an interdisciplinary “value network” of diverse players. Ranging from skilled individuals (the “citizen scientist” and the “garage entrepreneur”) and more established research institutions to companies with their infrastructures, equipment, and services, the novel platform approach enables all stakeholders to jointly contribute to value creation along more decentralized supply chain designs including research and technology development (RTD). A blockchain-enabled token economy efficiently leverages the “Wisdom of the Crowds” and secures “trust” and transparency by reputation systems requiring “skin in the game” from contributors. Prediction markets are created for guiding decision making, planning, and allocation of funding; competitive parallelization of work and its validation from independent participants substantially enhances quality, credibility, and speed of project outcomes in the real world along the entire path from RTD, fabrication, and testing to eventual commercialization. This novel, Blockchain-backed, open platform concept can be led by a corporation, academic entity, a loosely organized group, or even “chieflessly” within a smart-contract encoded Decentralized Autonomous Organization (DAO). The proposed strategy is particularly attractive for highly interdisciplinary fields like microfluidic Lab-on-a-Chip systems in the context of manifold applications in the Life Sciences. As an exemplar, we outline the centrifugal “Lab-on-a-Disc” technology. Rather than engaging in all sub-disciplines themselves, many smaller, highly innovative actors can focus on strengthening the product component distinguishing their unique selling point (USP), e.g., a particular bioassay, detection scheme, or application scenario. In this effort, system integrators access underlying commons like fluidic design, manufacture, instrumentation, and software from a more resilient and diversified supply chain, e.g., based on a verified pool of community-endorsed or certified providers.